2007
DOI: 10.1111/j.1467-2679.2007.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for cosmopolitan distribution of platyhelminth parasites of tunas (Thunnus spp.)

Abstract: Global distribution of platyhelminth parasites and their host specificities are not well known. Our hypothesis was that platyhelminth parasites of large pelagic fishes are common around the world. We analysed molecular variation in three different taxa of platyhelminth parasites infecting four species of tunas: yellowfin tuna (Thunnus albacares, Scombridae) from Western Australia, southern bluefin tuna (Thunnus maccoyii, Scombridae) from South Australia, Pacific bluefin tuna (Thunnus orientalis, Scombridae) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…Of the fish species reported to harbour species of Siphoderina, only Rachycentron canadum has a cosmopolitan distribution; it is thus possible that S. morosovi, which was reported from R. canadum, may also be widely distributed. Aiken et al (2007) recently reported near cosmopolitan distributions for species of Sanguinicolidae (confirmed by comparative analysis of rDNA sequence data) in bluefin tuna (Thunnus spp. ), so it is clear that trematodes of fishes can be widely distributed.…”
Section: Biogeographic Distributionmentioning
confidence: 99%
“…Of the fish species reported to harbour species of Siphoderina, only Rachycentron canadum has a cosmopolitan distribution; it is thus possible that S. morosovi, which was reported from R. canadum, may also be widely distributed. Aiken et al (2007) recently reported near cosmopolitan distributions for species of Sanguinicolidae (confirmed by comparative analysis of rDNA sequence data) in bluefin tuna (Thunnus spp. ), so it is clear that trematodes of fishes can be widely distributed.…”
Section: Biogeographic Distributionmentioning
confidence: 99%
“…Cardicola forsteri have recently become an emerging pathogen causing massive mortalities in cage-reared southern bluefi n tuna in coastal areas of Australia [ 119 , 120 ]. It has a big potential of further emergence in aquacultures in other parts of the world, being able to infect other tunas, like northern bluefi n suffering from cardicoliasis in Spanish coastal farms [ 100 ]. In Japan, mortality of pacifi c blue tunas is caused by C. orientalis and C. opisthorchis ; in a heavily infected individual, a total number of >4.5 million eggs were estimated in the gills at one side of the fi sh [ 121 ].…”
Section: Cardicolamentioning
confidence: 99%
“…in tuna fi shes ( Thunnus spp.) by molecular approaches [ 100 ]. Prevalence of the fl ukes in fi sh hosts varies greatly among various reports, and apparently, there is no common pattern.…”
Section: Occurrencementioning
confidence: 99%
“…Although A. laguncula has not been reported from any fish family on the GBR other than pomacentrids (reported from 3 species only), it has been recorded in 67 teleost species from 29 families, making it putatively one of the most widespread digeneans with respect to both geographical distribution and host range (Bray and MacKenzie 1990;Bray et al 1993a laguncula is indeed one species, despite its apparent cosmopolitan distribution, as has been previously demonstrated for the tuna-infecting aporocotylid fluke Cardicola forsteri Cribb, Daintith & Munday, 2000(Aiken et al 2007). The same principles may also apply to the other reportedly cosmopolitan species, Lecithaster stellatus.…”
Section: Host-specificitymentioning
confidence: 77%
“…(Aiken et al 2007), such widespread species appear to be exceptional. We think it possible, perhaps likely, that Pseudobacciger will prove to comprise a complex of significantly more species than are presently recognised.…”
Section: Taxonomymentioning
confidence: 99%